Early Greek poets' lives : the shaping of the tradition - Kivilo, Maarit. (Mnemosyne, Supplements, 2010)
This book examines the formation and development of the biographical traditions about early Greek poets, focusing on the traditions of Hesiod, Stesichorus, Archilochus, Hipponax, Terpander and Sappho. The study provides a detailed overview of the traditions and chronographical material about these poets and seeks to clarify who were the creators of the particular traditions; what were the sources; when the traditions were formed; and to what extent they are shaped by formulaic themes and story-patterns. It challenges several mainstream assumptions on the subject, for example, that the traditions were formed mainly in the Post-Classical period; that the only significant source for the legends is the works of the particular poet; and that the poets were perceived as "new heroes."